Karakterisasi Kekuatan Mekanik Komposit Berpenguat Serat Kulit Waru (Hibiscus Tiliaceus) Kontinyu Laminat Dengan Perlakuan Alkali Bermatriks Polyester - Nurudin, Arif; Sonief, Achmad As'ad; Atmodjo, Winarno Yahdi (Jurnal Rekayasa Mesin, 2011)
The purpose of this research is knowing the tensile strength and bending strength of polyester reinforced waru (Hibiscus tiliaceus) fiber composites with alkali treatment and variations in fiber orientation so we get the proper utilization of its strength properties. This composite material may be can replace fiberglass are expensive as reinforcement material in the process of making the ship’s hull.The method is performed by conducting alkalizationhibiscus fiber skin with 5% NaOH solution for 2 hours. In the manufacture of test specimensmade of composite test variations using four layers of fibers and fiber orientation angle is0o/45o/-45o/0o ; 45o/0o/0o/-45o ; 45o/0o/-45o/0o. Test object is made by hand lay-up and with anemphasis manually using a mold and press. Matrices are used polyester resin 157 BTQN and catalyst type MEKPO a concentration of 1%. Photo of specimen fracture was observed with amacro image observation. Mechanical properties are obtained from tensile tests and bending tests.The results showed that tensile strength and bending strength influence by alkali treatmentof NaOH 5%. Polyester reinforced waru fiber composite specimens with 5% NaOH treatment for2 hours is the same strength of attraction between the fiber direction angle of 0o/45o/-45o/0o is66.14 N/mm2; 45o/0o/0o/-45o is 66 ,46 N/mm2; and 45o/0o/-45o/0o is 66.78 N/mm2. Tensilestrength without alkali treatment is 49.13 N/mm2 on the fiber orientation direction 0o/45o/-45o/0o. The maximum bending strength obtained is 179.78 N/mm2 on the fiber orientation angle 0o/45o/-45o/0o with 5% NaOH alkali treatment. Bending strength of the lowest found in thedirection of fiber orientation angle 45o/0o/0o/-45o without alkali treatment is 134.43 N/mm2.Keywords: composite, waru fiber, alkalization, fiber direction